2017
DOI: 10.1073/pnas.1705463114
|View full text |Cite|
|
Sign up to set email alerts
|

Reassessing the atmospheric oxidation mechanism of toluene

Abstract: Photochemical oxidation of aromatic hydrocarbons leads to tropospheric ozone and secondary organic aerosol (SOA) formation, with profound implications for air quality, human health, and climate. Toluene is the most abundant aromatic compound under urban environments, but its detailed chemical oxidation mechanism remains uncertain. From combined laboratory experiments and quantum chemical calculations, we show a toluene oxidation mechanism that is different from the one adopted in current atmospheric models. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
136
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 189 publications
(149 citation statements)
references
References 64 publications
6
136
0
7
Order By: Relevance
“…On the other hand, continuum NPF occurs at low to intermediate levels of ambient PM 2.5 without significant capture of freshly nucleated particles and at a low growth rate without rapid increase in the surface area of nucleation-mode particles. In addition, photooxidation of vehicular exhaust (dominantly aromatic VOCs) yields abundant precursors for nucleation and growth of UFPs (29,32) as demonstrated in our three different types of measurements. Our ambient and chamber measurements are representative of typical urban environments worldwide (8) since the gasoline fleet of the commonly used vehicle model in China is equivalent to those in Europe and the United States (27).…”
Section: Discussionmentioning
confidence: 51%
“…On the other hand, continuum NPF occurs at low to intermediate levels of ambient PM 2.5 without significant capture of freshly nucleated particles and at a low growth rate without rapid increase in the surface area of nucleation-mode particles. In addition, photooxidation of vehicular exhaust (dominantly aromatic VOCs) yields abundant precursors for nucleation and growth of UFPs (29,32) as demonstrated in our three different types of measurements. Our ambient and chamber measurements are representative of typical urban environments worldwide (8) since the gasoline fleet of the commonly used vehicle model in China is equivalent to those in Europe and the United States (27).…”
Section: Discussionmentioning
confidence: 51%
“…Therefore, its reactions have been studied repeatedly, both experimentally and theoretically. A non-exhaustive list of recent studies can be found in references [5][6][7][8][9][10][11]. We have recently performed a detailed study of the possible routes for the reaction of toluene (T) with OH • , and further reactions of the intermediate radicals with both OH • and O2 [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…et al, 2001;Cameron et al, 2002;Steckler et al, 1997;Atkinson et al, 2006). Some addition (Steudel, 1995;Williams et al, 1983;Courmier et al, 2005;Zhang and Zhang, 2002), decomposition (Rayez et al, 2002;Kumar and Francisco, 2015;Gutbrod et al, 1996), isomerization (Zheng and Truhlar, 2010;Atkinson, 2007), and abstraction reactions (Ji et al, 2013;Ji et al, 2017) also are the important HAT reaction in the atmosphere. These atmospheric HAT reactions have a main feature that two-point hydrogen bond can occur and can facilitate hydrogen atom transfer (Kumar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%